HUBUNGAN PERILAKU PEMBELIAN DAN PEMBELIAN KOMPULSIF - Ina Oktaviana Matusin (Universitas Trisakti, 2007)
Consumer compulsive buying is an important area of inquiry in consumer behavior research. The importance of studying compulsive buying stems, in part, from its nature as a negative aspect of consumer behavior. Specifically, exploring negative consumption phenomena could provide modified or new perspectives for the study of positive consumption behaviors. Moreover, research on negative facets of consumption is useful because it can potentially contribute to society's wellbeing, an important criterion for usefulness of any research. This research builds on earlier papers to propose a model of compulsivity antecedents. Gender, consumers' tendency to make unplanned purchases, and their tendency to buy product not on shopping lists, serve to predict compulsive tendencies in a sample of Indonesian consumers. The findings suggest that these antecedents affect compulsive tendencies. The main purpose of this study is to examine the relationship between buying behavior and compulsive purchase tendency. This research use questionnaire which distribute to 120 respondents, 60 female and 60 male .The result of this research-shows that males will exhibit lower levels of compulsive purchase tendencies than females will.Keywords : Compulsive Buying, Costumer Behavior